Perbaikan Pengelolaan Badan Usaha Milik Desa Melalui Inisiasi Bisnis Baru Berbasis Ekonomi Sirkuler - Yudha Adi Kusuma; Mei Lenawati; Noordin Asnawai; Saufik Luthfianto (KREATIF: Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2025)
Village-owned enterprises (BUMDes) contribute to the village economy's improvement and independence. BUMDes management will face a variety of challenges. If we do not optimize BUMDes management, we cannot maximize the village's potential. A review of the selection of new businesses is necessary to ensure that BUMDes can once again boost village income. We are conducting a study on community service activities to enhance BUMDes management, with the aim of establishing a community recycling center. The types of community service activities include BUMDes management, community recycling center formation, and partnership strengthening. The community service activities employ methods that involve socialization and practice over a period of 4 weeks. The eval_uation and monitoring results showed that the combination method of combining socialization and practice had the highest impact on partners' knowledge of the circular economy, with an average value of 85.55. Testing with a one-way ANOVA can have a known sig value > 0.005, so that the results of each method used have the same variation. Following community service activities, we aim to establish a community recycling center and improve BUMDes management in Ngraket Village in the future.